Targeted drug therapy in non-small cell lung cancer: Clinical significance and possible solutions-Part I - Upadhya, Archana; Yadav, Khushwant S.; Misra, Ambikanandan (Expert opinion on drug delivery, 2021)
Non-small cell lung cancer (NSCLC) comprises of 84% of all lung cancer cases. The treatment options for NSCLC at advanced stages are chemotherapy and radiotherapy. Chemotherapy involves conventional nonspecific chemotherapeutics, and targeted-protein/receptor-specific small molecule inhibitors. Biologically targeted therapies such as an antibody-based immunotherapy have been approved in combination with conventional therapeutics. Approved targeted chemotherapy is directed against the kinase domains of mutated cellular receptors such as epidermal growth factor receptor (EGFR), anaplastic lymphoma kinases (ALK), neurotrophic receptor kinases (NTRK) and against downstream signaling molecules such as BRAF (v-raf murine sarcoma viral oncogene homolog B1). Approved biologically targeted therapy involves the use of anti-angiogenesis antibodies and antibodies against immune checkpoints. The rationale for the employment of targeted therapeutics and the resistance that may develop to therapy are discussed. Novel targeted therapeutics in clinical trials are also included. Molecular and histological profiling of a given tumor specimen to determine the aberrant onco-driver is a must before deciding a targeted therapeutic regimen for the patient. Periodic monitoring of the patients response to a given therapeutic regimen is also mandatory so that any semblance of resistance to therapy can be deciphered and the regimen may be accordingly altered.